Faktor yang memengaruhi minat mahasiswa berkarir sebagai konsultan pajak - Agista Dwi Praticha Nur Anjelia; Aisyaturrahmi Aisyaturrahmi (Akuntansi dan Teknologi Informasi, 2024)
The research was meticulously designed to investigate the impact of self-efficacy, job market considerations, financial rewards, and tax volunteer programs on students' interest in a career as a tax consultant. This study, based on quantitative primary data from questionnaire responses rated on a five-Likert scale, is a testament to the rigor of our research methodology. The research population comprises students from the Faculty of Economics and Universities in Surabaya who have participated in tax volunteering. The non-probability sampling technique, specifically the purposive sampling method, was employed to obtain 125 samples. The research data was rigorously analyzed using the Structural Equation Modeling – Partial Least Square. The findings of this research underscore the influence of self-efficacy and job market considerations on students' desire for a career as a tax consultant. On the other hand, the influence of financial rewards and tax volunteer programs on students' interest in a career as a tax consultant was found to be negligible. Potential for future research to broaden the scope of respondents and to include additional independent variables such as tax brevet training, offers hope for a more comprehensive understanding of the factors that influence student career interest.